Comparison of the Pharmacokinetics of Highly Variable Drugs in Healthy Subjects Using a Partial Replicated Crossover Study: A Fixed-Dose Combination of Fimasartan 120 mg and Atorvastatin 40 mg versus Separate Tablets - Hwang JG; Yu KS; Lee S (Dove Medical Press, 2020)
Jun Gi Hwang, Kyung-Sang Yu, SeungHwan Lee Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of KoreaCorrespondence: SeungHwan LeeDepartment of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 101 Daehak-ro, Jongno-gu, Seoul 03080, Republic of KoreaTel +82 2 2072 19200Fax +82 2 742 9252Email ksyu@snu.ac.krPurpose: A fixed-dose combination (FDC) of fimasartan and atorvastatin is used to treat hypertension and dyslipidemia. The peak plasma concentration (Cmax) of fimasartan and atorvastatin has a large intra-subject variability with a maximum coefficient of variation of 65% and 48%, respectively. Therefore, both drugs are classified as highly variable drugs. The purpose of this study was to compare the pharmacokinetics (PK) between a FDC of fimasartan 120 mg and atorvastatin 40 mg versus separate tablets in healthy male Korean subjects.Subjects and Methods: A randomized, single-dose, two-treatment, three-sequence, three-period, partial replicated crossover study was conducted with a 7-day washout interval between periods. Blood samples for fimasartan and atorvastatin were collected until 48 hours after administration in each period. PK parameters were calculated using the non-compartmental method. Geometric mean ratios (GMRs) for PK parameters of FDC to loose combination and their 90% confidence intervals (90% CIs) were estimated.Results: A total of 56 subjects completed the study. GMRs (90% CIs) of the Cmax for fimasartan and atorvastatin were 1.08 (0.93– 1.24) and 1.02 (0.92– 1.13), respectively. The expanded 90% CIs of both drugs using the intra-subject variability was calculated range of 0.70– 1.43 and 0.73– 1.38, respectively. The corresponding values of area under the concentration–time curve from zero to the last measurable time point were 1.02 (0.97– 1.08) and 1.02 (0.98– 1.07), respectively.Conclusion: FDC of fimasartan 120 mg and atorvastatin 40 mg between their loose combination showed similar PK characteristics.Keywords: fixed-dose combination, partial replicated design, fimasartan, atorvastatin, pharmacokinetics